Structural Design of CANs with Fine-Tunable Relaxation Properties: A Theoretical Framework Based on Network Structure and Kinetics Modeling - Konuray, Osman; Fernández-Francos, Xavier; Ramis, Xavier (Macromolecules, 2023)
In this work, we present a model capable of reproducing the stress relaxation dynamics of a wide range of relaxation processes in covalent adaptable networks (CANs) produced by stepwise polymerization. The proposed model captures the effective elastic response of the material subject to an initial stress by analogy with a network decrosslinking process. The combination of a recursive structural model and a kinetic model for the bond exchange reaction makes it possible to predict the expected stress relaxation profile in simple and complex systems depending on the structure of the network, the rate of bond exchange of the different components, and the presence of permanent bonds. After the basic features of the model are analyzed, its prediction capabilities are validated by simulating a number of scenarios taken from the literature. The results show that tailoring of the network architecture enables unprecedented flexibility in the design of CAN-based materials.